Heavy Metal Copper (Cu) Distribution in Water and Its Bioaccumulation in Green Mussel (Perna viridis) in Coastal Area of Ujung Pangkah, Gresik District - Qodri Fitra, Mohammad; Arfiati, Diana; Semedi, Bambang (Graduate School, Universitas Brawijaya, 2018)
Environmental pollution in the form of increased concentration of heavy metal Copper (Cu) becomes the main factor that can affect water quality and inhibit green mussel culture (Perna viridis) in Ujung Pangkah Coastal Area of Gresik District. The purpose of this research is to analyze concentration of heavy metal Copper (Cu) on water and its bioaccumulation in green mussel (P. viridis) in Ujung Pangkah waters, Gresik District. This research will be conducted from June to August 2017. The method used in this research is descriptive method. Sampling of seawater and mussel by purposive sampling. Cu heavy metal content in Ujung Pangkah waters, Gresik District has 0.003 - 0.006 ppm in July and 0.002 - 0.006 ppm in August. That value is still safe below predetermined quality standards. The results of heavy metal measurement test in shellfish has 0.159 to 0.69 ppm in July and 0.162 - 0.71 ppm in August. The high concentrations of Cu heavy metals in Ujung Pangkah waters are simultaneous to the bioaccumulation concentration in the green mussel. The higher concentration in the waters, the higher the bioaccumulation in the green mussels. And vice versa. The distribution of Cu heavy metal concentration at point 4 is the highest. While at point 1 has the lowest Cu heavy metal concentration. Keywords: Copper, Bioaccumulation, Green Mussel, Heavy Metal, Perna viridis.